(untitled) - Hibbert, Christopher (Harlow, 1970)
This is a narrative of the principal events in the troubled history of China's relations with the West during the final years of the Ch'ing dynasty. It has been written in the hope that as well as entertaining those unfamiliar with the story, it may provide some sort of historical background against which the modern Chinese view of the Western powers, and of their own place and importance in the world, may be more easily understood.
Keywords: Foreign relations; China